Lymph Node Cellular Dynamics in Cancer and HIV: What Can We Learn for the Follicular CD4 (Tfh) Cells? - Poultsidi, Antigoni; Dimopoulos, Yiannis; He, Ting-Fang; Chavakis, Triantafyllos; Saloustros, Emmanouil; Lee, Peter P.; Petrovas, Constantinos (Frontiers in Immunology, 2018)
Lymph nodes (LNs) are central in the generation of adaptive immune responses. Follicular helper CD4 T (Tfh) cells, a highly differentiated CD4 population, provide critical help for the development of antigen-specific B cell responses within the germinal center. Throughout the past decade, numerous studies have revealed the important role of Tfh cells in Human Immunodeficiency Virus (HIV) pathogenesis as well as in the development of neutralizing antibodies post-infection and post-vaccination. It has also been established that tumors influence various immune cell subsets not only in their proximity, but also in draining lymph nodes. The role of local or tumor associated lymph node Tfh cells in disease progression is emerging. Comparative studies of Tfh cells in chronic infections and cancer could therefore provide novel information with regards to their differentiation plasticity and to the mechanisms regulating their development.